261 MiR-326 regulates CD4+T cells differentiation in lupus disease of MRL/lpr mice. (April 2019) - Xia, Yuan; Fang, Xuan; Xiang, Nan; Dai, Xiaojuan; Jin, Li; Li, Xiaomei; Tao, Jinhui; Li, Xiangpei
Abstract : Background: CD4 +T cells play a major role in systemic lupus erythematous (SLE). Many aberrations in miR-326 expression have been described as related to abnormal T cell activation in SLE. The aim of this study was to investigate the effect of miR-326 expression on the differentiation of CD4 +T cells in MRL/lpr mice. Methods: 3 groups of female MRL/lpr mice were injected with lentivirus-miR-326 (LV-326) or lentivirus-miR-326 specific inhibitor (LV-sponge) to increase or inhibit miR-326 expression, respectively, and lentivirus-no-encoding (LV-ctrl) as control10 mice per group. The percentage of Th17, Th1, and Treg cells in spleen were determined by flow cytometry, the expression levels of CD4 +T related cytokines were determined by CBA and ELISA. Results: The results showed that, compared with LV-ctrl mice and LV-sponge mice, LV-326 mice had higher percentage of Th17 cells, and lower percentage of Tregs and Th1 cells in splenic CD4 +T cells. In contrast, LV-sponge mice had lower percentage of Th17 cells as well as higher percentage of Tregs and Th1 cells than LV-ctrl mice in splenic CD4 +T cells. Moreover, serum levels of IL-17A were significantly increased in LV-326 mice, compared with LV-ctrl mice and LV-sponge mice. Serum levels of IL-2 and TGF- were decreased in LV-326 mice compared with LV-ctrl mice. Conclusions: These findings suggesting that miR-326 regulates CD4 +T cells differentiation and inflammatory-related cytokines production in lupus model mouse. Implying that miR-326 may play a vital role in SLE pathogenesis by regulating CD4 +T cells differentiation. Funding Source(s): the National Natural Science Foundation of China (81373186)